Steroid profile in patients with breast cancer and in mice treated with mifepristone - Elia, Andres Maximiliano (2024)
Progesterone receptors (PRs) are biomarkers used as prognostic and predictive factors in breast cancer, but they are still not used as therapeutic targets. We have proposed that the ratio between PR isoforms A and B (PRA and PRB) predicts antiprogestin responsiveness. The MIPRA trial confirmed the benefit of 200 mg mifepristone, administered to patients with tumors with a high PRA/PRB ratio, but dose-ranging has not been conducted. The aim of this study was to establish the plasma mifepristone levels of patients from the MIPRA trial, along with the resultant steroid profiles, and compare these with those observed in mifepristone-treated mice using therapeutic schemes able to induce the regression of experimental mammary carcinomas with high PRA/PRB ratios: 6 mg pellets implanted subcutaneously, or daily doses of 12 mg/kg body weight. The plasma levels of mifepristone and other 19 plasma steroids were measured by liquid chromatography–tandem mass spectometry. In mifepristone-treated mice, plasma levels were lower than those registered in mifepristone-treated patients (i.e. day 7 after treatment initiation, pellet-treated mice: 8.4 ± 3.9 ng/mL; mifepristone-treated patients: 300.3 ± 31.7 ng/mL (mean ± s.d.; P < 0.001)). The increase in corticoid related steroids observed in patients was not observed in mifepristone-treated mice. The increase in progesterone levels was the most significant side effect detected in mifepristone-treated mice after 14 or 21 days of treatment, probably due to an ovarian compensatory effect not observed in postmenopausal patients. We conclude that in future clinical trials using mifepristone, the possibility of lowering the standard daily dose of 200 mg should be considered.